ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI DI KELAS X MADRASAH ALIYAH NEGERI 1 MEDAN - Nova Yunita Manik; Zulkifli Simatupang (Universitas Negeri Medan, 2017)
This research aims to determine how critical thinking skills and student learning outcome in biology subject (Ecosystem Chapter) and how the relationship between both of them in 1st Grade Madrasah Aliyah Negeri 1 Medan Learning Year 2015/2016. The population in this study is all of 1st grade student in Madrasah Aliyah Negeri 1 Medan Learning Year 2015/2016 totaling 390 student. The sampel method is purposive sampling with a sample 40 student. This research is a descriptive study, with a instrument (questionnaire) totaling 31 item about critical thinking skills and 36 item about student learning outcome with data collecting tools. From the analysis of student critical thinking data are categorized enough with 61-76 range limit by 22 student (55%) and student learning outcomes are also categorized enough with (62-77) range limit by 19 students (47,5%). Base on data requirement test known that there is a siqnificant positive relationship between critical thinking with student learning outcomes, but it have low correlation shown by the correlation coefficient percentage where the contribution percentage of 0,014% for critical thinking with student learning outcomes.Keywords: Critical Thinking, Learning Outcomes, Ecosystem